STUDY OF FISHING PORT FACILITIES REQUIREMENTS’S IN KUALA TERUSAN VILLAGE PANGKALAN KERINCI DISTRICT PELALAWAN REGENCY RIAU PROVINCE - Noval Novela; Nofrizal Nofrizal; Jonny Zain (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACK                This research takes Kuala Terusan Village as a case study on the study of fishing port facilities requirement. On February 2018 a measurement was conducted,aim to find out type and size or capacity fishing ports facilities which need tousing survey method.The village of Kuala Terusan is one of seven villages in Pangkalan Kerinci sub-district. Kuala Terusan village is a village that has a river in the upstream, this is why the river does not have a wave. Asresult of analysis of secondary data and primary that we conducted, requirement of facility landing place of fish are needed several facilities namelydock unloading, place of fish auction, fresh or clean air tank, oil fuel tank, shipyard and ice storage.Therefore, based on the researach finding, fishery port of Kuala Terusan village can be classified as an upstream river port. Upper River Port is a port located on a deep and wide river so that the vessel can enter upstream. Furthermore, the result of the research indicated that the length of loading docks required is 72.50 meters, 16.35meter length unloading dock. Extensive fish auction hall 50.9 meter2, capacity needs supplies [B1] amounting to fuel around [B2] 549 liters, 3394.5 liters fresh water tank and capacity 858 kilograms ice plants. From the results obtained that fishing ports be recommended is of type D is referred to as Fish Landing Base (PPI) or Fish Landing Place.Type jetty dock built will form a letter T which has a length of 72.50 meters, but due to location to be built dock is in the waters of the river that has a distance of 80 to 90 meters. Therefore the size of the dock to be built is divided into two and widen the size of the dock area so that can be used on the left and right side of the pier, with the length of the dock to be 36.25 meters. Keywords : Facility Type, Size Facilities, Fishing Port